1995
DOI: 10.1002/aja.1002030405
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for theMinallele ofApcresults in disruption of mouse development prior to gastrulation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 28 publications
(35 reference statements)
3
84
0
Order By: Relevance
“…It produces a stable truncated protein of 850 amino acids that lacks all ␤-catenin binding and other regulatory motifs (Su et al, 1992), leading to complete inability to bind and downregulate ␤-catenin, thus producing constitutively active ␤-catenin signaling. Complete loss of function of the Apc gene in Apc Min/Min embryos results in block of development at the 5.5-6.5 dpc stage and mutant embryos fail to form a pro-amniotic cavity or a primitive streak (Moser et al, 1995). This suggests that the patterning of the earliest phases of PD axis formation may also be susceptible to elevated ␤-catenin activity.…”
Section: Introductionmentioning
confidence: 92%
“…It produces a stable truncated protein of 850 amino acids that lacks all ␤-catenin binding and other regulatory motifs (Su et al, 1992), leading to complete inability to bind and downregulate ␤-catenin, thus producing constitutively active ␤-catenin signaling. Complete loss of function of the Apc gene in Apc Min/Min embryos results in block of development at the 5.5-6.5 dpc stage and mutant embryos fail to form a pro-amniotic cavity or a primitive streak (Moser et al, 1995). This suggests that the patterning of the earliest phases of PD axis formation may also be susceptible to elevated ␤-catenin activity.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, Apc +/Min mice have a low penetrance of extracolonic-manifestations such as mammary tumors, desmoids or cysts (Moser et al, 1993, Smits et al, 1998, Halberg et al, 2000. Homozygosity for this mutation leads to embryonic lethality at very early stages of gestation (6.5 dpc) (Moser et al, 1995). Accordingly, a similar mouse model, Apc ∆716 , carrying a targeted truncated mutation at codon 716 is also characterized by multiple intestinal tumors and no extra-intestinal manifestations (Oshima et al, 1995).…”
Section: Apc Dosage Effects In Tumorigenesismentioning
confidence: 99%
“…Die by 4 Weeks of Age-Because global inactivation of either the ␤-catenin gene (14,15) or Apc (16,17) results in early embryonic death, we crossed mice containing conditionally inactivatable alleles of ␤-catenin (␤-catenin-flox) (18) or Apc (Apc-flox) (19) to mice expressing cre under the control of the osteocalcin (OC) promoter (20) to disrupt these genes in osteoblasts. Previous analysis of the OC-cre strain via crossing it to strains carrying cre reporter transgenes indicated that expression of cre recombinase was specific to cells of the osteoblast lineage with no detectable expression or function in other cell lineages (20).…”
Section: Mice With Osteoblast-specific Deletions Of ␤-Catenin or Apcmentioning
confidence: 99%